(untitled) (REMUNOM, 2026)
This article examines intertextuality among literary narratives, contemporary rap, and cinema, framing it as a structuring mechanism of cultural production in contemporary society. Drawing on dialogism and intertextuality (Bakhtin, Kristeva) and transtextuality (Genette), alongside adaptation and intermediality studies (Hutcheon; Stam; Rajewsky), the analysis explores how quotation, allusion, sampling, remix, and audiovisual references shape meanings and symbolic disputes across media. Findings highlight four recurring axes of dialogue: (i) verbal/referential intertextuality through explicit citations and allusions; (ii) material/sonic intertextuality grounded in sampling and archival montage; (iii) audiovisual intertextuality through the appropriation of cinematic genres, framings, and iconographies; and (iv) structural intertextuality, in which narrative forms (voice, focalization, temporality, and dramatic arc) circulate across fields. The discussion argues that these intertextual relations perform both aesthetic and political functions: they build social memory, legitimize identities, rewrite canonical repertoires, and dispute the right to narrate peripheral experiences. The article concludes by proposing an interpretive model with three dominant modes—affiliation, conflict, and montage—useful for comparative readings in literary and cultural studies and for pedagogical practices in literary and media literacy.